(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article provides a comparative linguocultural and cognitive analysis of the concept of “labor” as represented in French and Uzbek folk proverbs. The study reveals the semantic, axiological, and pragmatic dimensions of the labor concept and identifies its role in the mentality of both cultures. Based on proverbial material, attitudes toward labor, social values, moral norms, and cultural stereotypes are examined. The findings demonstrate that in French culture labor is primarily associated with individual success and professional competence, whereas in Uzbek culture it is conceptualized as a moral and spiritual value symbolizing honesty, blessing, and prosperity.